Atsaru al-Khalfiyyah al-Ta'lîmiyyah 'alâ Mahârati al-Qirâati Ladâ Talâmîdzi al-Madrasah al-Mutawaasithah al-Islâmiyyah fî Bogor - Albantani, Azkia Muharom; Abdul Wahab, Muhbib; Farhati, Putri Amalia (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2023)
This study aims to determine the factors that cause students not to know the Arabic letters, to know the factors that cause students not to be able to read Arabic with good and correct pronunciation and also to determine whether there is an influence of students' educational background on reading ability (Jahriyyah). This study uses a quantitative approach with survey method. Data was collected using a questionnaire, interviews, and direct tests. The collected data were analyzed using percentage descriptive technique and simple linear regression analysis. The population in this study were students of 7th class at MTs Arrosyid II and 36 people as samples. Based on the results of the questionnaire research data, it was found that differences in students' educational backgrounds showed that the percentage of 72.1% was in the strong category. And from the results of the simple linear regression equation that there is an effect of students' educational background on reading ability, seen from Y = 19.889 + 0.806x and Ftable (0.05) > Fcount (0.008) the researcher can analyze that this equation shows a positive effect of variable X on variable Y and the influence of the remaining 19.1% is influenced by other variables. The factors that cause students not to know Hijaiyah letters are that they have not learned Arabic at their school before. The factors that cause students to be unable to read fluently are that they do not dare to express Arabic, do not trust themselves and are not interested in expressing Arabic